Historical Silencing and Epistemic In/Justice through the UNRWA Archive - Irfan, Anne (2023)
This article explores how historical silencing and epistemic in/justice occurs in and through the curation of UNRWA's central registry archive, now stored in Amman and previously located in Vienna, Gaza, and Beirut. Drawing on extensive work in the central registry and related archival collections, and critical archival theory, we show how the power dynamics of international aid, and the politics of the Palestine question, shape the collection's structure, content, and accessibility. We investigate the curation and selection of agency records, their organization, and their transparency or opacity to outsiders. In so doing, we illuminate how the curation of UNRWA's archive informs, shapes, and even distorts knowledge production on Palestinian refugee histories. By highlighting the interconnection between historical silencing and UNRWA's archives we expand understandings of the agency's complex, and at times contradictory, role in pursuing justice for Palestine refugees. Specifically, we unpack how the agency's curation of its archive can help promote its own preferred selfimage, and how this speaks to tensions at the heart of UNRWA's role.